MULTIMEDIA TECHNOLOGIES AS A MEANS OF IMPLEMENTATION OF PEDAGOGICAL SKILLS OF THE TEACHER OF MUSIC ART - Антоненко, М.М. (SWorldJournal, 2022)
The article the problem of pedagogical skill of a modern music teacher is considered. It is noted that the development and use of multimedia technologies in music lessons significantly expands the teacher’s creative field, increases the effectiveness of t